Business Ethics: Readings and Cases in Corporate Morality - W. Michael Hoffman, Robert E. Frederick (Mc Graw Hill, 2001)
This introductory text contains a thorough introduction to ethical theory, 54 readings, and 25 cases. Divided into five parts, each with an introduction which presents major themes of its articles and cases, the text contains an impartial, point-counterpoint presentation of different perspective on the most important and highly contended issues of business ethics. Each chapter ends with question that can be used for student discussion, review, tests or quizzes, or student assignments.